FIQIH OF JEWELLERY - Mohammad Adnan; Badrah Uyuni (Spektra: Jurnal Ilmu-ilmu Sosial, 2022)
Jewelry is anything that is used to decorate or beautify. Jewelry in the Qur'an and the Shari'a shows various meanings and automatically has various consequences. So in this study, the author tries to present fiqh for jewelry. It's just that what is focused in the discussion here is fiqh for what is generally known as jewelry by the general public. To discuss the ideas in this article, we use qualitative research methods, by making verses and hadiths to understand the concept of jewelry in Islamic law. Then also presented some opinions of scholars related to the jurisprudence of jewelry taken from various books of scholars. Journal articles and other supporting documents are also used to complement the discussions developed. And conceptually, God has adorned the human eye with a sense of love for everything that is desired, so that humans who love it will be willing to do everything in their power to get it. Jewelry in the life of the world is everything that is attached to humans, everything that accompanies humans and jewelry in the universe. All of that God created to be proof of His Oneness, a test for humans and a sunnah in worship. Thus, whether or not there is jewelry on a person, he does not feel hurt and must remain istiqomah in doing good.